Patterns and drivers of recent disturbances across the temperate forest biome. Issue 1 (December 2018) - Sommerfeld, Andreas; Senf, Cornelius; Buma, Brian; D'Amato, Anthony; Després, Tiphaine; Díaz-Hormazábal, Ignacio; Fraver, Shawn; Frelich, Lee; Gutiérrez, Álvaro; Hart, Sarah; Harvey, Brian; He, Hong; et al.
Abstract Increasing evidence indicates that forest disturbances are changing in response to global change, yet local variability in disturbance remains high. We quantified this considerable variability and analyzed whether recent disturbance episodes around the globe were consistently driven by climate, and if human influence modulates patterns of forest disturbance. We combined remote sensing data on recent (2001–2014) disturbances with in-depth local information for 50 protected landscapes and their surroundings across the temperate biome. Disturbance patterns are highly variable, and shaped by variation in disturbance agents and traits of prevailing tree species. However, high disturbance activity is consistently linked to warmer and drier than average conditions across the globe. Disturbances in protected areas are smaller and more complex in shape compared to their surroundings affected by human land use. This signal disappears in areas with high recent natural disturbance activity, underlining the potential of climate-mediated disturbance to transform forest landscapes. Climate change may impact forest disturbances, though local variability is high. Here, Sommerfeld et al. show that disturbance patterns across the temperate biome vary with agents and tree traits, yet large disturbances are consistently linked to warmer and drier than average conditions.